1985
DOI: 10.1177/0146167285111006
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Loneliness

Abstract: Earlier studies on gender differences in loneliness appear to have produced contradictory results. However, when 39 existing data sets were classified according to whether they used the UCLA scale (N = 28) or a self-labeling measure (N = II) of loneliness, the results revealed a clear pattern. Statistically significant sex differences are not usually found with the UCLA scale, but, when they are found, males typically have higher loneliness scores. In terms of self-labeling, women more frequently than men admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
240
5
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(306 citation statements)
references
References 19 publications
29
240
5
15
Order By: Relevance
“…Cramer & Neyedley (1998) conducted a study on sex Differences in Loneliness: The Role of Masculinity and Femininity and found that males tend to be lonelier than females but they are reluctant to admit it. This is supported by studies conducted by Bory & Perlman (1985), Wiseman, Guttfreund & Lurie (1995) and by Stokes & Levin (1986). This indicates that men and women use different standards in evaluating whether they are lonely.…”
mentioning
confidence: 60%
“…Cramer & Neyedley (1998) conducted a study on sex Differences in Loneliness: The Role of Masculinity and Femininity and found that males tend to be lonelier than females but they are reluctant to admit it. This is supported by studies conducted by Bory & Perlman (1985), Wiseman, Guttfreund & Lurie (1995) and by Stokes & Levin (1986). This indicates that men and women use different standards in evaluating whether they are lonely.…”
mentioning
confidence: 60%
“…Gender did not significantly impact on loneliness in the current investigation. Borys and Perlman (1985) argued that when loneliness is assessed indirectly, gender differences are generally not found. In this vein, it was expected that we would not find gender differences in the current study insofar as we assessed loneliness indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Bazı araştırmalarda cinsiyete göre yalnızlık açısından anlamlı bir fark olmadığı rapor edilmektedir ve bu sonuçlar mevcut araştırmanın bulgularıyla tutarlıdır (Jones, Freeman & Goswick, 1981;Williams, 1983;Wittenberg & Reis, 1986;Lamm & Stephan, 1987;Brage, Meredith & Woodward, 1993;Eren, 1994;Tarhan, 1996;Buluş, 1997;Demir ve Tarhan, 2001;Çeçen, 2008;Pancar, 2009;Çakır ve Çakır, 2011;İlhan, 2012;Oruç, 2013;Kılıç, 2014;Yalçın, 2015;Aktaş ve Yılmaz, 2017). Hem yurt içinde (Demir, 1990;Buluş, 1996;Saraçoğlu, 2000;Erözkan, 2004;Yıldırım, 2007;Duyan vd, 2008;Karaoğlu, Avşaroğlu ve Deniz, 2009;Şentürk, 2010) hem de yurt dışında (Borys & Perlman, 1985;Schultz & Moore, 1986;Medora, Woodward & Larson, 1987;McWhirter, 1990;Le Roux & Connors, 2001) yapılan araştırmaların büyük çoğunluğunda erkek öğrencilerin yalnızlık düzeylerinin kız öğrencilerden daha yüksek olduğu belirtilmektedir. Bu durum, erkek öğrencilerin ergenliğe özgü değişimleri, kız öğrenciler kadar çevresi ile paylaşma şansı bulamadığı için kendilerini daha fazla yalnız hissetmesi ile açıklanmaktadır (Duyan, vd.).…”
Section: Tartişma Ve Sonuçunclassified